1995
DOI: 10.1007/s001250050322
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of intraperitoneal insulin infusion using programmable implantable devices

Abstract: SummaryIntraperitoneal insulin infusion using implantable devices in insulin-dependent diabetic (IDDM) patients is promising since it improves diabetic control and decreases frequency of hypoglycaemia. However, preliminary data show a striking increase in plasma levels of anti-insulin antibodies with this therapy. In order to more precisely evaluate the immunogenicity and its consequences, anti-insulin antibody levels in 62 IDDM patients were assessed every 3 months during a 2-year period following pump implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 2 publications
2
28
1
Order By: Relevance
“…Several studies have shown that patients treated with insulin, develop significant insulin antibodies after some period and these subjects occasionally experience prolongation of insulin action, which produces nocturnal hypoglycemia and insulin resistance during the day period (Jeandidier et al, 1995). In the present study, we did not observe marked changes in the positive proportion of insulin antibodies level.…”
Section: Resultscontrasting
confidence: 51%
“…Several studies have shown that patients treated with insulin, develop significant insulin antibodies after some period and these subjects occasionally experience prolongation of insulin action, which produces nocturnal hypoglycemia and insulin resistance during the day period (Jeandidier et al, 1995). In the present study, we did not observe marked changes in the positive proportion of insulin antibodies level.…”
Section: Resultscontrasting
confidence: 51%
“…The high immunogenic response toward insulin reported by several authors in about half of the patients during IPII, together with the presence of amyloid deposits reacting with anti-insulin antibodies observed at the catheter tip, suggested that an immunological reactivity toward insulin could facilitate catheter obstruction (21)(22)(23). In our study, only one patient who had developed catheter obstruction exhibited a high plasmatic level of anti-insulin antibody.…”
Section: Influence Of Ipii Events On Macrophage Activationsupporting
confidence: 53%
“…Group 1 was composed of three diabetic patients (two men and one woman) aged 37-53 years (mean 45.6) who had been suffering from diabetes for 20.6 years on average (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. During the year after pump implantation, they presented with at least one episode of irreversible catheter obstruction, which led to the removal of the catheter.…”
mentioning
confidence: 99%
“…Another study reported that the development of insulin antibodies was associated with higher mean glucose values, higher postprandial glucose values and increased daily insulin requirements. Interestingly, two patients showed nocturnal falls in blood glucose despite stopping nocturnal insulin delivery, and in one of these patients, free insulin levels increased at night-time, from an average of 15 μU/ml during the day to 77 μU/ml at 24.00 h and 39 μU/ml at 04.00 h [10].…”
Section: Abbreviations Fpg: Fasting Plasma Glucosementioning
confidence: 99%